Anti-inflammatory and analgesic activities of Jateorhiza macrantha (Menispermaceae) - Glory Oluremilekun Ajayi,; O.A. Salako,; M.I Mosebolatan, (International Journal of Phytomedicine, 2015)
Jateorhiza macrantha (Hook.f.) Exell and Mendonça (Menispermaceae) is a common medicinal plant found in tropical Africa. Jateorhiza macrantha is used as an anti-hemorrhagic, to combat syphilis and headache. This study was performed to evaluate the analgesic and anti-inflammatory activities of its extract. The analgesic activity of the methanolic extract of Jateorhiza macrantha was investigated using the acetic acid (chemical) and tail-clip (mechanical) models of nociception in mice and the anti-inflammatory activity was investigated using the carrageenan-induced paw oedema in rats. In acetic acid-induced writhing test, the extract at doses 100, 200 and 400 mg/kg significantly (P < 0.05, 0.01) reduced the writhing reflex in a dose dependent manner. In the application of the metal artery clip unto the tail of animals, the extract caused a significant (P < 0.05) dose dependent increase in reaction latency with peak effect (7.0%) inhibition produced at the highest dose of 400 mg/kg. In the carrageenan induced paw oedema test, the extract produced a dose dependent significant (P < 0.05, 0.01, 0.001) inhibition of oedema. The results obtained in this study lend credence to the ethnomedicinal use of the plant in the management of pain and inflammatory conditions.